Dynamic drag of dislocations in aged aluminum alloys under laser irradiation - V.V. Malashenko (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов)
The above-barrier glide of dislocations under the action of laser pulses in aged aluminumиalloys containing nanoscale defects (Guinier-Preston zones) is theoretically analyzed. The problem is solved using a theory of dynamic interaction of defects. Analytical expressions for the dependence of the dynamic yield strength on the concentration of copper atoms and the dislocation density in the aged aluminum alloy has been obtained. The conditions for the occurrence of extrema of the functions describing the dependence of the dynamic yield strength of the aluminum alloy on the concentration of copper atoms and the dislocation density are analyzed. The analysis confirms the conclusions of the dynamic interaction of defects theory on the conditions for the occurrence of non-monotonic dependences of the mechanical properties of metals and alloys on the concentration of structural defects. The maximum occurs at the point where the main contribution to the formation of the spectral gap changes. The minimum is at the point where the main contribution to the dynamic drag of dislocations changes. It is shown that the nanoscale defects (Guinier-Preston zones) play an important role in the occurrence of two extrema of these dependences. The existence and position of the extrema are determined by the competition of the interaction of the moving dislocation with other dislocations of the ensemble, copper atoms and Guinier-Preston zones. Numerical estimates of the volume concentration of Guinier-Preston zones, at which the existence of two extrema is possible, are performed. According to estimates, the concentration of Guinier-Preston zones is of 1023-1024 m-3.